1998
DOI: 10.1046/j.1570-7458.1998.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore‐induced emissions of maize volatiles repel the corn leaf aphid, Rhopalosiphum maidis

Abstract: When maize plants, Zea mays L., are mechanically damaged and the damaged sites are treated with caterpillar regurgitant, the plants will release a specific blend of volatiles. It is known that these volatiles can be attractive to natural enemies of herbivores. We hypothesise that the plant volatiles constitute part of the induced plant defence and that herbivores will be affected by the odours as well. In laboratory and semi-field studies this hypothesis was tested for the aphid Rhopalosiphum maidis (Fitch) (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
159
1
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 228 publications
(172 citation statements)
references
References 43 publications
5
159
1
7
Order By: Relevance
“…For example, maize volatiles emitted from herbivore-damaged seedlings were shown to repel the corn leaf aphid (Rhopalosiphum maidis) (Bernasconi et al, 1998). However, in this study, we did not observe any repellence of early instar gypsy moth caterpillars by the major poplar volatile aldoximes (E/Z)-2-methylbutyraldoxime and (E/Z)-3-methylbutyraldoxime in the course of our olfactometer experiments ( Figure 7A).…”
Section: Poplar Aldoximes May Have Important Roles In Direct Defensecontrasting
confidence: 61%
“…For example, maize volatiles emitted from herbivore-damaged seedlings were shown to repel the corn leaf aphid (Rhopalosiphum maidis) (Bernasconi et al, 1998). However, in this study, we did not observe any repellence of early instar gypsy moth caterpillars by the major poplar volatile aldoximes (E/Z)-2-methylbutyraldoxime and (E/Z)-3-methylbutyraldoxime in the course of our olfactometer experiments ( Figure 7A).…”
Section: Poplar Aldoximes May Have Important Roles In Direct Defensecontrasting
confidence: 61%
“…HP GC Chemstation software was used to quantify all major components based on the known quantity of internal standards. Initial identification of most compounds was based on comparisons of retention times with those from previous studies (Bernasconi et al, 1998;Turlings & Benrey, 1998) and was confirmed with the mass spectrometry analysis of some samples. For this purpose 3 ll aliquot were injected in pulsed splitless mode into a GC, using the same column and temperature programme (Agilent 5973, transfer line 230°C, source 230°C, quadrupole 150°C, ionisation potential 70 eV, scan range 30-240 amu).…”
Section: Analyses Of Volatilesmentioning
confidence: 79%
“…The role of volatiles in the attraction of such natural enemies was first brought to light in studies on the interactions between arthropods and plant leaves. Results revealed that herbivore attack induces emissions of volatile organic compounds (VOC) attractive to parasitoids and predators Sabelis 1988, Turlings et al 1995;De Moraes et al 1998), and this role of induced volatiles in tritrophic interactions has also been demonstrated under realistic field conditions (Bernasconi et al 1998;De Moraes et al 1998;Thaler 1999;Kessler and Baldwin 2001). While the aboveground portion of a plant is obviously essential for photosynthesis and reproduction, the root system is also of vital importance.…”
Section: Introductionmentioning
confidence: 99%